2014
DOI: 10.1093/nar/gku474
|View full text |Cite
|
Sign up to set email alerts
|

PARP-2 and PARP-3 are selectively activated by 5′ phosphorylated DNA breaks through an allosteric regulatory mechanism shared with PARP-1

Abstract: PARP-1, PARP-2 and PARP-3 are DNA-dependent PARPs that localize to DNA damage, synthesize poly(ADP-ribose) (PAR) covalently attached to target proteins including themselves, and thereby recruit repair factors to DNA breaks to increase repair efficiency. PARP-1, PARP-2 and PARP-3 have in common two C-terminal domains—Trp-Gly-Arg (WGR) and catalytic (CAT). In contrast, the N-terminal region (NTR) of PARP-1 is over 500 residues and includes four regulatory domains, whereas PARP-2 and PARP-3 have smaller NTRs (70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
322
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(349 citation statements)
references
References 40 publications
26
322
0
1
Order By: Relevance
“…The DNA-dependent activity of these DDR PARPs requires the presence of a conserved Tyr-Gly-Arg (WGR) domain, which is present in PARPs 1-3 (Langelier et al, 2012;Langelier et al, 2014). In addition to the WGR domain, PARP1, which is perhaps the most structurally complex member of the PARP family, also contains these regulatory domains: the breast cancer susceptibility protein-1 C terminus (BRCT) domain and three zinc finger domains (ZnF1-3) (Figure 2) Steffen et al, 2013).…”
Section: Dna-dependent Parpsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DNA-dependent activity of these DDR PARPs requires the presence of a conserved Tyr-Gly-Arg (WGR) domain, which is present in PARPs 1-3 (Langelier et al, 2012;Langelier et al, 2014). In addition to the WGR domain, PARP1, which is perhaps the most structurally complex member of the PARP family, also contains these regulatory domains: the breast cancer susceptibility protein-1 C terminus (BRCT) domain and three zinc finger domains (ZnF1-3) (Figure 2) Steffen et al, 2013).…”
Section: Dna-dependent Parpsmentioning
confidence: 99%
“…PARP1 can also be activated by binding nucleosomes as well as abnormal DNA structures, such as DNA overhangs, hairpins, forks, and cruciform structures Langelier and Pascal, 2013;Langelier et al, 2012Langelier et al, , 2014. Adding further complexity, PARP1 can also be activated by interacting with its binding partners, such as phosphorylated ERK2, thus affecting further downstream signaling cascades or by being modified by a number of posttranslational modifications (Cohen-Armon et al, 2007).…”
Section: Dna-dependent Parpsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA bağlayan bölge olan N-terminal uç, hasarlı DNA'yı onarmaktan sorumludur. Mer- (15). PARP aktivasyonunun ilişkili olduğu bazı olaylar Tablo 2'de sunulmuştur (16,17).…”
Section: Poli (Adp-riboz) Polimerazlar (Parp'lar)unclassified
“…Recent studies found that PARP-3 could be stimulated by DNA double-strand breaks (DSBs) in vitro and functioned in the same pathway as the poly (ADPribose)-binding protein APLF to accelerate chromosomal DNA DSB repair [9][10][11]. As a result, the absence of PARP3 confers hypersensitivity to anti-tumoral drugs generating DSB [11][12]. However, the underline molecular events remained elusive.…”
Section: Introductionmentioning
confidence: 99%